(untitled) (European Journal of Mental Health, 2014)
Sándor Karácsony (1891–1952) was an original, creative and influential representative of Hungarian pedagogical, linguistic and philosophical thinking. As a secondary school teacher and a university professor he established a new school of thought with a lasting impact. The principle underlying his philosophy was that in education, in scientific research, and in all areas of life ‘the other person’ must be taken into account if we are to achieve valid results. In the 1970s and 1980s his former disciples and co-workers achieved significant results in various fields of science and education, such as mathematics, biology, linguistics, psychology and ethnography by applying and further developing his ideas, and many of them have also been responsible for new schools of scientific thought. Karácsony’s pedagogical thinking is very much alive even today. Representatives of the third and fourth generations of teachers who are familiar with Karácsony’s ideas believe that education takes place as a joint achievement of teacher and student if the two partners have respect for each other’s autonomy, and on this basis they relate to the ideals and values of the school. After 1990 his disciples and their co-workers created several social organisations dedicated to the task of making his work known again to those concerned. A part of this work was re-editing his ten-volume educational theory based on interpersonal logic and interpersonal psychology, and in the past 23 years holding conferences to present his pedagogical principles, which continue to be valid even today, to teachers, students and parents.